QuEChERS extraction followed by enzyme-linked immunosorbent assay for determination of deoxynivalenol and zearalenone in cereals. Issue 6 (2nd November 2017) - He, Qiurong; Peng, Hongwei; Yang, Jinyi; Xu, Zhenlin; Fan, Congcong; Sun, Yuanming
ABSTRACT: A simple, rapid and cost-effective QuEChERS method for the determination of ZEN and DON by ELISA in cereals was developed. The single factor experiment was used to ﬁnd the optimal QuEChERS parameters (extraction solvent, extraction method, extraction time, the QuEChERS composition, sorbent and clarification time) and extracts were analysed by ELISA. The optimised method was validated for selectivity, linearity, limits of detection, matrix effect and precision. The recovery values of ZEN and DON by ELISA were compared with a standard HPLC method and the results showed good coefficient with HPLC, which proved to be suitable for the screening of cereal samples for the presence of ZEN or DON. This is the ﬁrst report of the determination of ZEN and DON in cereals after QuEChERS extraction combined with the enzyme-linked immunosorbent assay method.